The Problem of Translating Participles from German into Serbian - Redžović, Elma H. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Not only are the systemic differences of these two languages decisive, but also the ways of using language conditions in actual speech use are different. The present participle in German serves as a substitute for relative clauses, and when used as an attribute, it gets the number and gender from the noun it refers to. It also changes according to the adjective declension, so a noun can be easily made from it. The perfect participle in German serves to build complex past verb tenses and passives, and can have both adverbial and adjectival uses. Participles in the Serbian language are verbal adverbs and verbal adjectives. The structure and use of the perfect participle is not a problem for those who learn German, because the participle in the Serbian language is built on a similar grammatical principle. The passive is very rarely used in the Serbian language, so the German passive in the Serbian language corresponds to impersonal reflexive structures, reflexive passive, passive-participle or active. That is why special attention is paid to the passive forms in the German language.In the process of translation, it is important to remain consistent with the structure of the original text and not to deviate much. In fact, with the help of various literary analyses and reviews, translators can overcome many challenges. It is important to firstly interpret what the poet wanted to say and only then approach a certain translation task.
Keywords: language system; participle; translating; German; text; Serbian